2015
DOI: 10.1016/j.jaci.2014.12.1353
|View full text |Cite
|
Sign up to set email alerts
|

Use of Omalizumab for Treatment of Antihistamine and Steroid Resistant Chronic Idiopathic Urticaria during Pregnancy

Abstract: RATIONALE: Information on the clinical profile of CIU/CSU in adolescents is limited. Baseline characteristics and demographics of an adolescent subgroup of CIU/CSU patients enrolled in randomized, placebo-controlled omalizumab trials are evaluated. METHODS: This is a post-hoc descriptive analysis of pooled baseline data from three omalizumab trials in CIU/CSU patients who remained symptomatic despite H 1 -antihistamine treatment [and H 2 -antihistamines and/or leukotriene receptor antagonists (LTRA) in one stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A total of 67 observational studies on the effectiveness of omalizumab in CIU (with or without angioedema) were identified (Figure 1). As detailed in eTable 1 in the Supplement, there were 19 studies of patients with CIU or CSU specified, 2 of patients with chronic autoimmune urticaria (CAU), 5 of patients with chronic urticaria not otherwise specified (CU NOS), 38 of patients with CIU, CSU, or CU NOS with comorbidities, and another 3 of mixed samples of patients with urticaria. These articles on the effectiveness of omalizumab in CIU were included in our group’s systematic review, which also contains additional study description, narrative analysis, and tables of evidence …”
Section: Methodsmentioning
confidence: 99%
“…A total of 67 observational studies on the effectiveness of omalizumab in CIU (with or without angioedema) were identified (Figure 1). As detailed in eTable 1 in the Supplement, there were 19 studies of patients with CIU or CSU specified, 2 of patients with chronic autoimmune urticaria (CAU), 5 of patients with chronic urticaria not otherwise specified (CU NOS), 38 of patients with CIU, CSU, or CU NOS with comorbidities, and another 3 of mixed samples of patients with urticaria. These articles on the effectiveness of omalizumab in CIU were included in our group’s systematic review, which also contains additional study description, narrative analysis, and tables of evidence …”
Section: Methodsmentioning
confidence: 99%